Sequelae following an epidemic of meningococcal meningitis in Niger in 2022 - Abdoul-Aziz Idrissa; Salifou Atti; Roger Kiamvu Wasaulua; Serge Kazadi; Ousmane Sani; Elhadji Ibrahim Tassiou; Ousmane Guindo; Georges Tonamou; Iza Ciglenecki; Matthew E. Coldiron (PLoS ONE, 2025)
Background The management of post-meningitis sequelae is a priority in the WHO Roadmap to Defeat Meningitis by 2030. Nonetheless, the prevalence of sequelae in the African Meningitis Belt is not well described, making the development of post-meningitis care programmes difficult. We conducted a home-based follow-up study of cases notified during an epidemic due to Neisseria meningitidis serogroup C (NmC) in 2022 in the Dungass and Magaria Districts of Niger, to describe the prevalence of sequelae several months after the epidemic. Methods Standard WHO case definitions were used during the epidemic. District linelists were completed with the results of PCR testing of patients who had undergone lumbar puncture. These lists included the village of origin of the notified cases. Accompanied by community outreach workers, the study’s nurse-investigators sought out case-patients in their homes to assess the presence of sequelae. A standardised questionnaire was administered, and a focused physical examination was carried out. Results A total of 1001 suspected cases and 50 deaths (CFR 5.0%) were reported in the two districts. A total of 469 CSF samples (47%) were analysed at the national reference laboratory, of which 220 were PCR positive (47%). NmC was the predominant causative organism (87% of confirmed cases). 82 cases were excluded due to distance. 570 of the 919 cases sought out were eventually found and included. Of these 570 cases, 49 had died (CFR 8.6%). Among surviving cases, the prevalence of sequelae was 12%, and among survivors of confirmed NmC meningitis, 18%. The most common sequelae were hearing loss (6%), paralysis (3%) and epilepsy (2%). Discussion Case fatality during the epidemic appears to have been higher than reported in routine surveillance. The prevalence of severe sequelae is high, and clinical description of sequelae could help future epidemic management.